First records of the subfamilies Ecliminae and Lomatiinae (Diptera, Bombyliidae) from China with description of two new species - Yao, Gang; Luo, Jun; Li, Xuankun; Yang, Ding (Zootaxa, 2022)
Two subfamilies of bee flies, Ecliminae and Lomatiinae, are first reported from China with the description of the following two new species: Lomatia shanguii sp. nov. and Thevenetimyia cingulata sp. nov. A key to the Chinese subfamilies of Bombyliidae and a key to the Palaearctic species of Thevenetimyia Bigot are also presented.